A Practical Framework for Constructing Structured Drawings - Cheema, Salman; Buchanan, Sarah; Gulwani, Sumit; Jr., Joseph J. LaViola (IUI'14, February 24 - 27 2014, Haifa, Israel, 2014)
We describe a novel theoretical framework for modeling structured drawings which contain one or more patterns of repetition in their constituent elements. We then present PatternSketch, a sketch-based drawing tool built using our framework to allow quick construction of structured drawings. PatternSketch can recognize and beautify drawings containing line segments, polylines, arcs, and circles. Users can employ a series of gestures to identify repetitive elements and create new elements based on automatically inferred patterns. PatternSketch leverages the programming-by-example (PBE) paradigm, enabling it to infer non-trivial patterns from a few examples. We show that PatternSketch, with its sketch-based user interface and a unique pattern inference algorithm, enables efficient and natural construction of structured drawings.